Olympic Games, Mega-Events and Civil Societies
XIII, 292 p.
Keywords: This volume explores sporting mega-events, their social, political, and cultural characters, the value systems that they inscribe and draw on, the claims they make on us and the claims the organisers make for them, the spatial and ethical relationships they create, and the responses of civil societies to them.